Efficacy of a multicomponent binding agent against combined exposure to zearalenone and ochratoxin A in weaned pigs - Tassis, Panagiotis; Raj, Jog; Floros, Dimitrios; Mittas, Nikolaos; Ntarampa, Niki; Farkas, Hunor; Polizopoulou, Zoe; Vasilievic, Marko (Frontiers in Veterinary Science, 2024)
The aim of the study was to evaluate the efficacy of a novel multicomponent substance against combined exposure to the mycotoxins zearalenone (ZEN) and ochratoxin A (OTA) in weaned piglets. In total 60 piglets at the age of 28 days, were equally allocated to four experimental groups (A-D) consisting of eight female and seven male piglets each (15 animals per group, trial duration of 42 days). Animals from group A received typical weaners feed without mycotoxins or the test product [multicomponent mycotoxin detoxifying agent (MMDA)]. Group B animals received the same weaners feed contaminated with 0.992 mg ZEN/kg feed, and 0.531 mg OTA/kg feed without the addition of the MMDA. Animals in group C received the same contaminated feed with group B with the addition of 1.5 g MMDA/kg feed, whereas group D received the same feed as group B with the inclusion of 3 g MMDA/kg feed. Clinical signs and performance parameters [body weight (BW), average daily weight gain (ADWG), feed conversion ratio (FCR)] were evaluated, whereas mycotoxin residues were also assessed in liver and kidney tissues. Findings showed improved FCR in the group that received the greatest dose of the test product (3 g MMDA/kg feed) in comparison to the group which received the lower dose (1.5 g MMDA/kg feed). Few hematological and biochemical parameters were slightly altered, predominantly within normal limits. Residue analysis demonstrated a reduction of OTA in liver samples, a-ZEL in liver and total tested samples, as well as of total ZEN and metabolites contents in all samples of the group that received the greatest MMDA dose in comparison to the group which received the toxins without the addition of the test product. Therefore, a positive effect of the MMDA at the greatest dosage regime on reducing bioavailability and tissue deposition of ZEN and OTA with a particular positive effect on FCR in weaned pigs is suggested under concurrent ZEN and OTA exposure in vivo.